Apreciative Inquiry dalam Membangun Hubungan Interpersonal antar Divisi Karyawan Di Rumah Sakit XYZ - Rosidah Lawazhim (CV. Syntax Corporation Indonesia, 2022)
One of the causes of work stress is bad interpersonal relationships between employees. Interpersonal relationships are interactions that are built by employees in work situations with the aim of working together productively. The condition of the organization in this hospital has problems between other divisions that trigger a less harmonious relationship. This causes interpersonal relationships with other divisions to be uncomfortable and miscommunication occurs. This is also one of the problems of conflict within the company that occurs in various forms and styles, which hinders the relationship of individuals with groups or larger groups. Therefore the aim is to know the impact of the given manipulation. Manipulation given in experimental research is the provision of treatment or intervention. the research method used, experimental research is research by manipulating the respondent's condition with the aim of knowing the impact of the manipulation given. Manipulation given in experimental research is the provision of treatment or intervention. The experimental design used is a pretest-posttest control group design, which is a form of experimental research using two groups, namely the experimental group and the control group, where the experimental group is given treatment while the control group is not treated. The results showed that the experimental group that was given the Appreciative Inquiry treatment got a higher score than the control group. Based on the results of the quantitative analysis that has been carried out, it can be concluded that the hypothesis proposed in this study is accepted, namely Appreciative Inquiry can improve interpersonal relationships between employees at XYZ Hospital. This can be proven from the results of the study which showed that the experimental group that was given the Appreciative Inquiry treatment got a higher score than the control group.